β-Hydroxybutyrate Mitigated Heart Failure with Preserved Ejection Fraction by Increasing Treg Cells via Nox2/GSK-3β - Liao S (Dove Medical Press, 2021)
Shengen Liao,1,* Yuan Tang,1,* Xin Yue,1 Rongrong Gao,1 Wenming Yao,1 Yanli Zhou,1 Haifeng Zhang2,3 1Department of Cardiology, The First Affiliated Hospital of Nanjing Medical University, Jiangsu Province Hospital, Nanjing, 210029, People’s Republic of China; 2Department of Cardiology, The Affiliated Suzhou Hospital of Nanjing Medical University, Suzhou Municipal Hospital, Gusu School, Nanjing Medical University, Suzhou, 215002, People’s Republic of China; 3Department of Cardiology, Jiangsu Province Hospital, Nanjing, 210029, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haifeng ZhangDepartment of Cardiology, The Affiliated Suzhou Hospital of Nanjing Medical University, Suzhou Municipal Hospital, Gusu School, Nanjing Medical University, Suzhou, 215002, People’s Republic of ChinaEmail haifeng_zhang@163.comBackground: This study was designed to investigate the cardioprotective role of β-hydroxybutyrate (BHB) in heart failure with preserved ejection fraction (HFpEF) and the underlying mechanism.Methods: A two-hit model with a high-fat diet (HFD) and Nω-nitrol-arginine methyl ester (L-NAME) was used as an HFpEF model. The treatment group received a weekly intraperitoneal injection of β-hydroxybutyrate (BHB). Cardiac function, inflammation, and fibrosis were evaluated. CD3+CD4+Foxp3+ positive cells within the myocardium were quantified by flow cytometry. The NADPH oxidase 2 (NOX2)/glycogen synthase kinase-3β (GSK3β) pathway was examined by immunoblot analysis.Results: BHB improved diastolic function, fibrosis and cardiac remodeling in HFpEF. Additionally, BHB inhibited cardiac inflammation and increased cardiac Treg cells, which could be due to the downregulation of the NOX2/GSK-3β pathway.Conclusion: BHB protected against the progression of HFpEF by increasing cardiac Treg cells by modulating the NOX2/GSK-3β pathway.Keywords: β-hydroxybutyrate, HFpEF, Treg cells, NOX2, GSK-3&#x03B2